STUDI GAYA KEPEMIMPINAN DAN DINAMIKA KELOMPOK PADA POKDAKAN BAYUR SEJAHTERA DI KELURAHAN SEMPAJA UTARA KOTA SAMARINDA - Idris Kusuma Wijaya; Erwiantono; Nurul Ovia Oktawati (2339-1324, 2020)
The purpose of this research is to know the characteristics, levels of group dynamics, members ' perception of leadership style, and level of satisfaction to the group's leadership style, And know the relationship between characteristics, group dynamics and leadership style to the satisfaction of group members. Research conducted in bayur village, sempaja north of samarinda city. The sample method used is the census method and the data analysis used is qualitative descriptive analysis and rank Spearman. The results of the analysis showed the characteristics of the management and group members including the 25-34 years age group, the majority of high school education. non-formal education 3 – 4 times meeting, the income range of 1,600,000 – 2,100,000, the majority of the long 3 years and status is married. The group's dynamic rate is medium with an average interval value of 92.26. Perception of group leader leadership style is in relaxed leadership style with a quadrant value of 72%, And the level of satisfaction of group leader leadership in the category is satisfied with an average of 79.46. The results of the correlation seen that the characteristic variable with level of satisfaction have a relationship that is very weak, while the dynamics of the group to the level of satisfaction has a strong relationship and very significantly, as well as the leadership style to the level of satisfaction have a relationship that is moderate and significant